Post-Holocaust politics : Britain, the United States & Jewish refugees, 1945-1948 - Kochavi, Arieh J. (University of North Carolina Press, 2001)
Between 1945 and 1948, more than a quarter of a million Jews fled countries in Eastern Europe and the Balkans and began filling hastily erected displaced persons camps in Germany and Austria. As one of the victorious Allies, Britain had to help find a solution for the vast majority of these refugees who refused repatriation. Drawing on extensive research in British, American, and Israeli archives, Arieh Kochavi presents a comprehensive analysis of British policy toward Jewish displaced persons and reveals the crucial role the United States played in undermining that policy. Kochavi arg.